2010
DOI: 10.1111/j.1549-0831.2009.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Highway Expansion on Population Change: An Integrated Spatial Approach

Abstract: The effects of highways on transforming human society and promoting population change have been investigated in several disciplines, including geography, sociology, economics, and planning. Currently, the primary highway construction activity in the nation is highway expansion; however, this expansion has not been the focus of much of the existing literature. This research examines the role that highway expansion plays in the process of population change. Specifically, this research proposes an integrated spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 45 publications
8
95
0
5
Order By: Relevance
“…Analysing the effect of roads on the growth of population in 275 Metropolitan Statistical Areas of continental USA between 1980 and 2000, Duranton and Turner (2012) suggest that the increases in the major road stock can explain why some areas experienced higher population growth than others. Chi (2010), examining the effects of highway "expansions" on population change in Wisconsin during the 1980s and 1990s, suggests that highway expansions mostly influenced population increase in suburban areas, thereby strengthening suburbanisation. On the other hand, Henry et al (1997) report that the initial stock of highways at 1980 was unrelated with population growth in rural hinterland tracts in South Carolina, Georgia and North Carolina during the 1980s.…”
Section: The Impact Of Road Infrastructure On Lu Changementioning
confidence: 99%
“…Analysing the effect of roads on the growth of population in 275 Metropolitan Statistical Areas of continental USA between 1980 and 2000, Duranton and Turner (2012) suggest that the increases in the major road stock can explain why some areas experienced higher population growth than others. Chi (2010), examining the effects of highway "expansions" on population change in Wisconsin during the 1980s and 1990s, suggests that highway expansions mostly influenced population increase in suburban areas, thereby strengthening suburbanisation. On the other hand, Henry et al (1997) report that the initial stock of highways at 1980 was unrelated with population growth in rural hinterland tracts in South Carolina, Georgia and North Carolina during the 1980s.…”
Section: The Impact Of Road Infrastructure On Lu Changementioning
confidence: 99%
“…Research findings have suggested that population growth (or decline) is determined jointly by demographic, social, economic, political, geographic, and cultural forces as well as temporal and spatial influences [4]. However, the majority of existing research is focused on only some of the factors and influences and does not consider others [5]. This might be due to the fact that development and population change are complex and require interdisciplinary knowledge, but existing studies are often conducted within disciplinary boundaries [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Jenelius (2009), Weiping and Chi (2010), while spatial availability of road network in selected regions was presented by Liu and Yu (2012), and Pantha et al (2010). Of the papers dealing with population distribution in the context of traffic networks and roads, Chi (2010), Kotavaara et al (2011), and Morency et al (2011) can be mentioned. Relations between spatial units and their subsequent analyses are frequent topics of numerous scientific studies.…”
Section: Introductionmentioning
confidence: 99%